Circular business model implementation: Design choices, orchestration strategies, and transition pathways for resource-sharing solutions. (20th January 2021) - Palmié, Maximilian; Boehm, Jonas; Lekkas, Charlotte-Katharina; Parida, Vinit; Wincent, Joakim; Gassmann, Oliver
Abstract: Prominent political and societal stakeholders argue that business models (BMs) are pivotal in making a successful transition to a circular economy (CE). However, the existing CE literature has paid little attention to design choices that allow companies to implement circular business models (CBMs) that meet the requirements of their specific situations. Resource sharing (alternatively called asset sharing) is a key practice in making the transition to a CE. The present article, therefore, seeks to gain deeper insights into the CBMs of firms that orchestrate resource-sharing solutions. For this purpose, it uses a qualitative multiple case-study approach and analyzes nine firms that orchestrate virtual power plants in Germany and Switzerland. Specifically, the article explores the design choices with which firms are faced when they implement CBMs, and it examines different implementation strategies that flow from making certain design choices. The article also identifies transition pathways that enable firms to move between different implementation strategies in order to increase economic and environmental gains. The present article can serve as a stimulus for further detailed analyses of other BMs that are important to a CE in the future.